2008
DOI: 10.1097/scs.0b013e3180f6112f
|View full text |Cite
|
Sign up to set email alerts
|

Successful Blood Conservation During Craniosynostotic Correction With Dual Therapy Using Procrit and Cell Saver

Abstract: Skin tumors comprise the largest group of malignancies of the head. Despite the accessibility of such lesions, the treatment of neglected, far advanced cancers, many of which have extended deeply into the facial bones and skull, is often required. The key to the cure of malignant tumors of the head is an accurate diagnosis and evaluation of the margins of an excised tumor. Reconstructive surgery of the head after resection of tumors requires a complete understanding of the anatomy of this region. From January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 11 publications
1
55
0
Order By: Relevance
“…THA was no longer a predictor for allogeneic blood transfusion, as this group had more percentage of patients with a preoperative haemoglobin level <120 g/dl and female gender. discussion Intra-operative blood salvage avoids problems with the storage of pre-donated autologous blood and allogeneic blood transfusion, and enables retransfusion of more efficacious oxygen-carrying red blood cells that have a higher erythrocyte viability 23 and increased preservation of 2-3 diphosphoglycerate. 24 It also removes contaminants and concentrates the re-transfusion volume.…”
Section: Resultsmentioning
confidence: 99%
“…THA was no longer a predictor for allogeneic blood transfusion, as this group had more percentage of patients with a preoperative haemoglobin level <120 g/dl and female gender. discussion Intra-operative blood salvage avoids problems with the storage of pre-donated autologous blood and allogeneic blood transfusion, and enables retransfusion of more efficacious oxygen-carrying red blood cells that have a higher erythrocyte viability 23 and increased preservation of 2-3 diphosphoglycerate. 24 It also removes contaminants and concentrates the re-transfusion volume.…”
Section: Resultsmentioning
confidence: 99%
“…Krajewski and colleagues administered EPO 3 weeks, 2 weeks, and 1 week preoperatively and used Cell Saver intraoperatively; there was a marked increase in preoperative hematocrit and lower transfusion rates. 20 Fearon and Weinthal administered EPO weekly for 3 weeks preoperatively and found an increased hemoglobin level and reduced blood transfusion. 10 Meneghini et al performed acute preoperative normovolemic hemodilution in addition to administering EPO for 3 weeks before surgery and found a decreased transfusion rate.…”
Section: Discussionmentioning
confidence: 99%
“…9 As previously mentioned, Krajewski et al found significantly reduced transfusion rates with the use of EPO and Cell-Saver. 20 In our study, all but 3 infants in the protocol group and none in the control group received recycled autologous blood. The protocol group had a significantly lower transfusion rate, consistent with previous studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Peri-operative red cell salvage re-infuses fresh blood and avoids the problems with storage of red blood cells seen with autologous pre-donation and allogeneic red blood cells. This translates to more efficacious oxygen carrying red blood cells with a higher mean erythrocyte viability [27] and increased preservation of 2-3 diphosphoglycerate [28]. The technique also incorporates washing the blood loss volume.…”
Section: Intra-operative Strategiesmentioning
confidence: 99%